Wall to Wall. - Gillick, Liam; Serpentine Gallery, London; Southampton City Art Gallery, Southampton; Leeds City Art Gallery, Leeds (London : South Bank Centre, 1994)
Baumgarter, Lothar ; Craig-Martin, Michael ; Diamond, Jessica ; Kruger, Barbara ; Toroni, Niele ; Weiner, Lawrence ; Barry, Robert ; Buren, Daniel ; LeWitt, Sol ; Patterson, Simon ; Roberts, Julie ; Van Der Stokker, Lily ; Bulloch, Angela ; Caramelle, Ernst ; Gordon, Douglas ; Graf, Franz ; Gussin, Graham ; Tremlett, David ; Wood, Craig
Wall to Wall, Serpentine Gallery, London, 19 January to 27 February 1994 ; Southampton City Art Gallery, Southampton, 22 April to 5 June 1994 ; Leeds City Art Gallery, Leeds, 12 May to 2 July 1994
boek